Non ordinary process of schooling. A qualitative study of their protagonists’ perceptions - Hidalgo , Nina; Cerrillo, Rosario; Lizana Peinado, Ignacio; López Bueno, Helena (Revista Complutense de Educación, 2023)
Enrollment in extraordinary period or student mobility is one of the processes least addressed from research in the educational field (Carrasco et al., 2012). Some authors (Aramburu, 2002; Bonal y Zancajo, 2020; Piemontese, 2018) affirm that it is a highly complex process and it tends to generate school segregation. For this, this study aims to know the process of students’ admission in extraordinary period of a municipality in the south of Madrid from the perspective of its protagonists. To achieve this, a case study has been developed with six semi-structured interviews with school principals, representatives of the AMPA and representatives of the community of Madrid and the city council. The results show that there is great dissatisfaction with the enrollment process outside the ordinary period, especially because it generates an imbalance between schools as families choose the center to take their children (which has places). This situation increases the differences between the centers that fill their enrollment in the ordinary period and those that receive students throughout the school year, promoting school disparity and with it, educational inequality.
Keywords: Case study; educational inequality; enrollment in extraordinary period; school segregation